Quality local seeds to farmers: Supporting seed system development in Uganda and Nepal - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
Seed is a critical input for agricultural production. In many developing countries, limited access to and availability of quality seeds affects farmers’ food and nutrition security and impedes efforts to make agrifood systems more productive, inclusive, environmentally sustainable, and nutrition sensitive. Research on seed systems is a key component of the CGIAR Research Program on Policies, Institutions, and Markets (PIM). Two recent outcomes of this work include the revision and implementation of the seed in Uganda and the registration of 11 local varieties of beans, rice, fingermillet, proso millet, amaranth and cucumber used by farmers in Nepal. Both achievements contribute to enhanced quality assurance for popular varieties commercialized by farmers at the local level.